2021
DOI: 10.1002/hep.32152
|View full text |Cite
|
Sign up to set email alerts
|

Aging exaggerates acute‐on‐chronic alcohol‐induced liver injury in mice and humans by inhibiting neutrophilic sirtuin 1‐C/EBPα‐miRNA‐223 axis

Abstract: Background and Aims: Aging exacerbates liver neutrophil infiltration and alcohol-associated liver disease (ALD) in mice and humans, but the underlying mechanisms remain obscure. This study aimed to examine the effect of aging and alcohol consumption on neutrophilic Sirtuin 1 (SIRT1) and micro-RNA-223 (miR-223), and their contribution to ALD pathogeneses. Approach and Results: Young and aged myeloid-specific Sirt1 knockout mice were subjected to chronic-plus-binge ethanol feeding. Blood samples from healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…Therefore, miR-223 inhibits neutrophil infiltration and protects against alcohol-induced liver injury. Interestingly, the neutrophilic miR-223 expression level was lower in aged mice than in young mice [ 214 ]. Aging stimulates the susceptibility to acute and chronic alcohol-induced liver injury by inhibiting the neutrophilic SIRT1-C/EBPα-miR-223 axis.…”
Section: Oxidative Stress-related Pathogenic Mechanisms Of Aldmentioning
confidence: 99%
“…Therefore, miR-223 inhibits neutrophil infiltration and protects against alcohol-induced liver injury. Interestingly, the neutrophilic miR-223 expression level was lower in aged mice than in young mice [ 214 ]. Aging stimulates the susceptibility to acute and chronic alcohol-induced liver injury by inhibiting the neutrophilic SIRT1-C/EBPα-miR-223 axis.…”
Section: Oxidative Stress-related Pathogenic Mechanisms Of Aldmentioning
confidence: 99%
“…Aging as a risk factor has been shown to modify the development and progression of ALD 39 . In our previous study, aging increases the susceptibility of alcohol-induced liver injury by downregulating sirtuin 1 (SIRT1) in hepatocytes and hepatic stellate cells, and the SIRT1-C/EBPα-miR-223 axis in neutrophils 7 , 8 . The ASK1-signalosome network is a major center of stress signals that plays multiple roles in promotion of senescence, aging and diseases of oxidative stress 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Aging is associated with progressive changes in hepatic structure and function, and also increases the risk of various types of liver diseases, including ALD, non-alcoholic liver disease, liver fibrosis and liver cancer 6 . Our previous studies have shown that aged mice have a high susceptibility to ethanol-induced liver damage, mainly manifested by excessive inflammation and oxidative stress 7 , 8 . In addition, it has been documented that activation of stress kinases plays critical role in the progression of ALD 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The factors that influence these transcription factors are also involved in miR-223 expression. For example, Sirtuin-1, an NAD + -dependent histone deacetylase, interacts with C/EBPα to induce its deacetylation, thereby inducing miR-223 expression in neutrophils ( 13 ). Meanwhile, macrophage colony-stimulating factor and receptor activator of nuclear factor kappa-B ligand can increase expression of PU.1 ( 14 ).…”
Section: Mir-223 Biosynthesis and Functionmentioning
confidence: 99%
“…A recent study showed that aging increases the susceptibility of alcohol-induced liver injury in both mice and humans via downregulation of the SIRT1-C/EBPα-miR-223 axis in neutrophils ( 13 ). When circulating neutrophils were obtained from both middle-aged and elderly subjects, levels of SIRT1 and miR-223 were found to be lower than in circulating neutrophils obtained from young individuals.…”
Section: Mir-223 In Liver Diseasesmentioning
confidence: 99%